Factors Contributing to False Negative Results when Performing Diagnostics of COVID-19 by Reverse Transcription-Polymerase Chain Reaction in Real Time - A. A. Petrov; T. E. Sizikova; N. V. Karulina; O. V. Chuhralya; D. I. Paveliev; N. A. Saifulina; A. V. Sapkulov; V. N. Lebedev; D. A. Kutaev; S. V. Borisevich (Вестник войск РХБ защиты)
Reverse transcription-real-time polymerase chain reaction (RT-PCR) is currently the leading laboratory diagnostic tool for COVID-19. With the help of RT-PCR-RT, diagnostics is carried out at the early stages of the development of the disease. The studied clinical samples, as a rule, are swabs from the pharynx and nasopharynx. The aim of the work is to identify and analyze the factors that contribute to false negative results when diagnosing COVID-19 by RT-PCR-RT. It is shown in the article, that the analytical sensitivity of the real-time RT-PCR method is not the main factor in assessing the possibility of obtaining false negative results. The paper considers the effect of drinking hot drinks (tea, coffee), alcohol and smoking (immediately before sampling) on the results of the analysis of swabs from the pharynx and nasopharynx by RT-PCR RT. It was found that the intake of hot drinks before sampling (the probability of obtaining a false negative result is at least 80%) influences most of all on the possibility of obtaining a false negative result in RT-PCR-RT in swabs from the pharynx. The use of small doses of alcohol (0.25–0.33 g of ethanol per 1 kg of body weight) has a lesser effect. Smoking immediately prior to sample collection does not lead to a false negative result in real-time RT-PCR. None of the considered influences affects the possibility of obtaining false negative results in the analysis of swabs from the nasopharynx. Recommendations were made on the need for simultaneous examination of both throat swabs and nasopharyngeal swabs in the ongoing diagnosis of COVID-19.